Pelatihan Kemasan Produk UMKM di Desa Mekarmanik Kecamatan Cimenyan Kabupaten Bandung Jawa Barat: MSMEs Product Packaging Training in Mekarmanik Village Cimenyan Subdistrict Bandung Regency - Suminartika, Eti; Hapsari, Hepi; Deliana, Yosini (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The role of small-scale business (UMKM) is source of income and job for the people. The problem of the industry is low quality of product packaging. The purpose of PKM are: (1) How to increase the knowledge and (2) how to raise packaging practice. PKM activities took place from June 24th until July 24th, 2024. The activity was done by companionship of lecture, demonstration and practice. Participant knowledge and practice increase were analysed based pre-test before activity and post-test after activity. The result of activity showed us there were increase significantly about packaging product knowledge and packaging product experience.